Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve this problem, we need to find two positive consecutive odd integers whose product is 143.
Let's denote the greater odd integer by [tex]\( x \)[/tex]. Since the integers are odd and consecutive, the smaller odd integer would then be [tex]\( x - 2 \)[/tex].
The product of these two integers can be represented by the equation:
[tex]\[ x(x - 2) = 143 \][/tex]
Now, let's set up the equation:
[tex]\[ x(x - 2) = 143 \][/tex]
Expanding this, we get:
[tex]\[ x^2 - 2x = 143 \][/tex]
Rearranging it into standard form of a quadratic equation:
[tex]\[ x^2 - 2x - 143 = 0 \][/tex]
To solve this quadratic equation, we can use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 1 \)[/tex], [tex]\( b = -2 \)[/tex], and [tex]\( c = -143 \)[/tex].
Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
[tex]\[ \Delta = (-2)^2 - 4 \cdot 1 \cdot (-143) \][/tex]
[tex]\[ \Delta = 4 + 572 \][/tex]
[tex]\[ \Delta = 576 \][/tex]
Now, find the roots:
[tex]\[ x = \frac{2 \pm \sqrt{576}}{2} \][/tex]
[tex]\[ x = \frac{2 \pm 24}{2} \][/tex]
This gives us two solutions:
[tex]\[ x_1 = \frac{26}{2} = 13 \][/tex]
[tex]\[ x_2 = \frac{-22}{2} = -11 \][/tex]
Since we are looking for positive integers, we discard [tex]\( -11 \)[/tex] and accept [tex]\( 13 \)[/tex] as the solution.
Thus, the greater integer is:
[tex]\[ \boxed{13} \][/tex]
Let's denote the greater odd integer by [tex]\( x \)[/tex]. Since the integers are odd and consecutive, the smaller odd integer would then be [tex]\( x - 2 \)[/tex].
The product of these two integers can be represented by the equation:
[tex]\[ x(x - 2) = 143 \][/tex]
Now, let's set up the equation:
[tex]\[ x(x - 2) = 143 \][/tex]
Expanding this, we get:
[tex]\[ x^2 - 2x = 143 \][/tex]
Rearranging it into standard form of a quadratic equation:
[tex]\[ x^2 - 2x - 143 = 0 \][/tex]
To solve this quadratic equation, we can use the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 1 \)[/tex], [tex]\( b = -2 \)[/tex], and [tex]\( c = -143 \)[/tex].
Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac \][/tex]
[tex]\[ \Delta = (-2)^2 - 4 \cdot 1 \cdot (-143) \][/tex]
[tex]\[ \Delta = 4 + 572 \][/tex]
[tex]\[ \Delta = 576 \][/tex]
Now, find the roots:
[tex]\[ x = \frac{2 \pm \sqrt{576}}{2} \][/tex]
[tex]\[ x = \frac{2 \pm 24}{2} \][/tex]
This gives us two solutions:
[tex]\[ x_1 = \frac{26}{2} = 13 \][/tex]
[tex]\[ x_2 = \frac{-22}{2} = -11 \][/tex]
Since we are looking for positive integers, we discard [tex]\( -11 \)[/tex] and accept [tex]\( 13 \)[/tex] as the solution.
Thus, the greater integer is:
[tex]\[ \boxed{13} \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.